2000
DOI: 10.1506/8cp5-xayg-7u37-h7vr
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing and Audit Risk for Internal Audit Services*

Abstract: Some companies now outsource their internal audit function to public accountants. Internal auditors and accounting firms disagree about the merits of outsourcing. Each type of auditor claims to provide more cost‐effective services and appears to claim superior expertise. This paper uses agency theory to examine outsourcing and reconciles the outsourcing debate without resorting to differential auditor expertise. Under the assumptions that public accountants' “deep pockets” provide incentives to outsource and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 24 publications
1
28
1
1
Order By: Relevance
“…Consistent with these contradictory arguments, empirical research provides inconsistent evidence, with some results favoring an inhouse IAF (Coram et al, 2008;Johl et al, 2013;Munro & Stewart, 2010) and others an outsourced IAF (Abbott et al, 2012;Ahlawat & Lowe, 2004;Christ et al, 2015;Desai et al, 2011;Glover et al, 2008;Prawitt et al, 2012). Despite these contradictory arguments and evidence, outsourcing IAF practice is a rapidly growing phenomenon (Caplan & Kirschenheiter, 2000). Carey et al (2000) reported that 45% of their study sample outsourced part or all IAF activities.…”
Section: Prior Research and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with these contradictory arguments, empirical research provides inconsistent evidence, with some results favoring an inhouse IAF (Coram et al, 2008;Johl et al, 2013;Munro & Stewart, 2010) and others an outsourced IAF (Abbott et al, 2012;Ahlawat & Lowe, 2004;Christ et al, 2015;Desai et al, 2011;Glover et al, 2008;Prawitt et al, 2012). Despite these contradictory arguments and evidence, outsourcing IAF practice is a rapidly growing phenomenon (Caplan & Kirschenheiter, 2000). Carey et al (2000) reported that 45% of their study sample outsourced part or all IAF activities.…”
Section: Prior Research and Hypothesis Developmentmentioning
confidence: 99%
“…This is consistent with prior external audit and IAF literature that suggested Big4 audit firms are able to provide a higher quality audit than other types of auditor. (e.g., Caplan & Kirschenheiter, 2000;DeAngelo, 1981;Francis, Maydew, & Sparks, 1999;Francis & Yu, 2009;Munro & Stewart, 2010). We use audit fees and audit report lag to identify audit efficiency, and use 711 observations from companies listed on the Omani capital market to test our hypotheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While rotation might improve the quality of reporting (Christ et al 2015), it could discourage employees and newcomers from joining IA teams by pointing to the general nature of the IA work (Bartlett et al 2016). In a similar vein, studies exploring outsourcing of IA to third parties suggest that outsourcing improves the independence and objectivity of IA, but discourages auditee managers from sharing information, resulting in lower audit quality (Abdolmohammadi 2013;Caplan et al 2000;Prawitt et al 2012;Speklé et al 2007). Overall, these studies reveal that due to lack of content knowledge on the heterogeneity of processes (including risk management, corporate governance, and internal control), IA has developed its techniques to merely verify the process of decision-making (Pentland 2000;Power 1999).…”
Section: Ia Expansions To New Domainsmentioning
confidence: 99%
“…There has been extensive research on the importance of an internal control function as part of an effective corporate governance structure. Prior internal audit research has evaluated: objectivity issues (Church and Schneider ; Brody and Lowe ; Stewart and Sabramaniam ); the interaction between internal and external audit (Stein et al ; Brody et al ; Felix et al ; Mihret and Admassu ; Prawitt et al ); the trend to outsource internal audit functions (Caplan and Kirschenheiter ; Dickins and O'Reilly ; Majdalawieh and Alkafaji ); and the relationship between internal audit and the audit committee (Leung et al ; Christopher et al ; Davies ; Sarens et al ).…”
Section: Literature Reviewmentioning
confidence: 99%